(untitled) (MAUSAM, 1964)
It is generally recognised that the presence of salt nuclei in clouds has a powerful influence on rain formation. It is with a view to find out whether continuous diffusion of salt nuclei into air from a powerful atomizer, placed at a height of 60 ft above ground, which is fed by salt solution and worked by compressed air at 20 atmospheres would have any effect on local rainfall, that experiments were undertaken at the Jadavpur University in 1958 and 1959. The atomizer was kept in continuous action throughout the day-light hours during April to October of 1958 and during July to October of 1959. During 1958 and 1959, West Bengal had deficient monsoon rainfall. The departures of rainfall from the normal in each of the months, during which the experiments were done, were plotted and the lines of equal departures were drawn. These showed that the curves of least negative departures and in some cases highest positive departures were generally oval-shaped extending from north of Calcutta to a distance of about 100 miles towards the prevailing wind direction in all the months in which the experiments were done. This suggested that this oval-shaped area received more rainfall than the neighbouring areas. As this area came under the influence of the salt nuclei which permeated into the air and a fair proportion of which reached cloud levels after a travel of short distance from south Calcutta, it is considered that this factor may have contributed to the increase in rainfall.